Pembiasaan Ibadah Melalui Program Kegiatan Keagamaan Mingguan Di Lingkungan MAN 2 Deli Serdang - Hermalia Putri; Mavianti (Journal of Development Education and Learning (JODEL), 2026)
This study aims to analyze the habituation of worship through weekly religious programs at MAN 2 Deli Serdang as a strategy for developing students’ religious character. The research is based on the finding that students’ worship practices tend to be formal and have not been fully internalized in daily life. A descriptive qualitative approach was employed using observation, interviews, and documentation as data collection techniques. The participants included the principal, Islamic education teachers, religious supervisors, and students. The findings indicate that weekly religious activities such as Qur’anic recitation, congregational prayers, short sermons, and dhuha prayers function as effective habituation mechanisms that enhance students’ discipline, consistency in worship, and spiritual awareness. The program’s effectiveness is supported by teachers’ role modeling, time management integrated with academic schedules, and institutional policies. However, obstacles remain, including low intrinsic motivation among students and external environmental influences. This study concludes that the habituation of worship through structured weekly religious programs significantly contributes to the internalization of religious values and the formation of students’ spiritual character. Penelitian ini bertujuan untuk menganalisis pembiasaan ibadah melalui program kegiatan keagamaan mingguan di MAN 2 Deli Serdang sebagai strategi pembentukan karakter religius siswa. Latar belakang penelitian ini didasarkan pada temuan bahwa praktik ibadah siswa masih bersifat formal dan belum terinternalisasi secara konsisten dalam kehidupan sehari-hari. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Informan penelitian meliputi kepala madrasah, guru Pendidikan Agama Islam, pembina keagamaan, dan siswa. Hasil penelitian menunjukkan bahwa program keagamaan mingguan yang meliputi tadarus Al-Qur’an, shalat berjamaah, kultum, dan shalat dhuha berperan sebagai stimulus pembiasaan yang efektif dalam meningkatkan kedisiplinan, konsistensi ibadah, serta kesadaran spiritual siswa. Keberhasilan program didukung oleh keteladanan guru, pengaturan waktu yang terintegrasi dengan kegiatan akademik, dan dukungan kebijakan madrasah. Namun, masih ditemukan hambatan berupa rendahnya motivasi intrinsik siswa dan pengaruh lingkungan luar sekolah. Penelitian ini menyimpulkan bahwa pembiasaan ibadah melalui program keagamaan mingguan berkontribusi signifikan terhadap internalisasi nilai religius dan pembentukan karakter spiritual siswa.